A Reflective Study of Computerized Database Application Technology and Maintenance - Yang, Shiqi (International Journal of Computer Science and Information Technology, 2024)
In the era of digitalization, computer databases have become an indispensable technological support across various industries. They not only house a vast amount of data but also enable efficient management and swift retrieval of this information. Concurrently, advancements in database application technology and maintenance have become crucial in ensuring the stable operation of information systems. However, contemporary computer database technology still faces numerous challenges such as data compatibility, automation levels, and flexibility in data transmission. Therefore, this study focuses on the key application techniques and maintenance mechanisms of computer databases, exploring measures to enhance data compatibility, improve production automation, strengthen the flexibility of data transmission, and bolster technical support. These efforts aim to drive the development of computer databases towards efficiency, stability, and security, thus laying a solid data foundation for the sustainable development of the entire information society.